Possible prevention of post‐partum depression by intake of omega‐3 polyunsaturated fatty acids and its relationship with interleukin 6. Issue 4 (15th February 2021) - Nagayasu, Yoko; Fujita, Daisuke; Daimon, Atsushi; Nunode, Misa; Sawada, Masami; Sano, Takumi; Ohmichi, Masahide
Abstract: Aim: This study examined whether the intake of omega‐3 polyunsaturated fatty acids (PUFA) prevented post‐partum depression and if interleukin 6 (IL‐6) was involved in this effect. We hypothesized that omega‐3 supplementation has a protective effect against post‐partum depression. Methods: We measured eicosapentaenoic acid (EPA), the arachidonic acid (AA)/EPA ratio, and IL‐6 in 80 singleton pregnant women during the first and second trimesters, and post‐partum. The women also completed a dietary questionnaire, and post‐partum depression was measured using the Edinburgh Postnatal Depression Scale (EPDS). We examined the correlations between the frequency of eating fish and EPA, the AA/EPA ratio and IL‐6 in the first and second trimesters, and post‐partum. We also investigated the correlation between the EPDS and the EPA, the AA/EPA ratio and IL‐6. Results: The frequency of eating fish was significantly correlated with EPA in the second trimester and post‐partum and with the AA/EPA ratio in the second trimester. There was no correlation between IL‐6 levels and the frequency of eating fish. Post‐partum levels of EPA and the AA/EPA ratio were higher in the EPDS >7 group than in the EPDS ≤7 group. In the second trimester, a higher AA/EPA ratio was associated with EPDS >7. IL‐6 levels did not differ between the two groups. Conclusion: In conclusion, a low dietary intake of omega‐3 PUFA during pregnancy was correlated with lower EPA levels, which tended to lead to post‐partum depression. The relationship between the IL‐6 level and the pathogenesis of post‐partum depression was unclear from the results of this study.